Pengalaman lansia dalam penanganan inkontinensia urin di wilayah kerja puskesmas Kamonji - Collein, Irsanty (Jurusan Keperawatan FIKES UNSOED, 2012)
The aging process is an unique process that occurs to all human influencing by biological, psychological, social, functional and spiritual factors. The aging process that occurred to each human will cause disruption or decreased of human function that influence individual’s health status. The aim of this research was to get the depth understanding about elderly experience to urinary incontinence treatment in health community center of Kamonji work area. The research design was a phenomenological qualitative with the design of exploratory descriptive. The data was analized by Collaizy technique (1978) that consist of 7 (seven) steps. Number of participants who joined this research were 2 (two) elderly people by the age of > 90. This research result carried out 3 (three) themes that were urinating everywhere, nothing special precaution to cope with wetting, the health workers never informed about the treatment. The conclusion was found 3 (three) themes of elderly experience to urinary incontinence treatment.